METHODOLOGY OF TEACHING SIMULTANEOUS INTERPRETATION - Fayziyeva S. Y. (Academia Science Repository, 2023)
The article discusses the fundamentals of simultaneous interpreting, the prerequisites for practicing simultaneous interpreting, and the expertise needed by interpreters. The paper also discusses efficient lessons for teaching simultaneous interpreting.